Pengaruh Kepercayaan dan Kualitas Pelayanan terhadap Minat Masyarakat Membayar ZIS di LAZ Rumah Zakat Pusat - Khalwani, Abdullah Mushlihuddin (Sharia Economics Study Program Faculty of Islamic Economics and Business UIN Sunan Gunun, 2024)
In Indonesia, the inadequate realization of zakat, infaq and sadaqah (ZIS) capabilities requires specific attention. This is caused by several problems that need to be addressed with concrete solutions. Increasing public intention in paying ZIS through amil zakat institutions (LAZ) is one of the solutions. To reach these refinements, it is significant to build trust and provide quality services. The purpose of this study is to analyze the effect of trust and service quality on public intention in paying ZIS through LAZ Rumah Zakat Pusat.This research utilizes a quantitative approach with multiple linear regression analysis techniques. The findings of this study are that trust and service quality have a positive and significant effect on interest in paying ZIS at LAZ Rumah Zakat Pusat.